Pengaruh Harga, Kualitas Produk, Lokasi Dan Minat Masyarakat Muslim Terhadap Permintaan Produk Yafa’s Beauty & Health Care : Studi Kasus Klinik Kecantikan Yafa’s Kota Medan - Sari, Deva Kumala; Nurbaiti, Nurbaiti; Nasution, Juliana (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to measure the price, product quality, location and interest of the muslim community to the demand for products either partially, simultaneously or interaction. This study uses quantitative research, with an associative approach. The population in this study is the customer beauty clinic Yafa's beauty health & care in Medan.Sampling in this study using saturated Sampling techniques. Data collection techniques by distributing questionnaires (questionnaire).The Data used in this study are primary data, data analysis techniques used are data validity test, data reliability test, classical assumption test, and hypothesis test.The results showed that partially variable price, product quality, location and interest of the Muslim community positively and significantly influenced the demand for Yafa's beauty health & care products. Then testing the hypothesis variable price, product quality, location and interest of the Muslim community simultaneously positive and significant effect on product demand Yafa's beauty health & care. From the calculation of the coefficient of determination shows that the variable product demand is influenced by price, product quality, location, interest of the muslim community by 62%.